2022
DOI: 10.3390/en15218272
|View full text |Cite
|
Sign up to set email alerts
|

Automated Classification of Pipeline Defects from Ultrasonic Phased Array Total Focusing Method Imaging

Abstract: The defects in the welds of energy pipelines have significantly influenced their safe operation. The inefficient and inaccurate detection of the defects may give rise to catastrophic accidents. Ultrasonic phased array inspection is an important means of ensuring pipeline safety. The total focusing method (TFM), using ultrasonic phased arrays, has become widely used in recent years in non-destructive evaluation (NDE). However, manual defect recognition of TFM images is seen to lack accuracy and robustness, aris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In addition, physicians identified concerns with the accuracy and reliability of HBP devices as a key factor hindering the recognition of HBPM by physicians and patients. This could be attributed to the lack of instructions on device calibration in the local guidelines of most countries/regions, except for China, Indonesia, and Japan [15][16][17]. As with all devices, it is important to ensure HBP monitors are calibrated and Local guidelines should advocate using calibrated HBPM devices and provide specific instructions on calibration to support accurate measurements [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, physicians identified concerns with the accuracy and reliability of HBP devices as a key factor hindering the recognition of HBPM by physicians and patients. This could be attributed to the lack of instructions on device calibration in the local guidelines of most countries/regions, except for China, Indonesia, and Japan [15][16][17]. As with all devices, it is important to ensure HBP monitors are calibrated and Local guidelines should advocate using calibrated HBPM devices and provide specific instructions on calibration to support accurate measurements [18].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that, while a high proportion of physicians recommended HBPM to their patients, discrepancies between HBPM recommendations in guidelines and practice realities were prevalent. For instance, all of the countries/regions surveyed, except for the Philippines, recommended 135/85 mmHg as the diagnostic threshold for hypertension by HBP in general population in their guidelines (Supplementary Table 4) [15][16][17][19][20][21][22][23][24][25][26]. However, overall, only one-fifth of the physicians cited 135/85 mmHg as the diagnostic threshold for HBPM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro-ultrasonic phased array is widely applied in medical testing [1,2] and industrial inspection [3,4], because of its nondestructive detection mode. The micro-ultrasonic phased array is mainly composed of a piezo element, an electrode, a matching layer, and a flexible circuit [5], where the role of the * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%